Pharmacokinetics of Tobramycin in Patients with Stable Renal Impairment, Patients Undergoing Peritoneal Dialysis, and Patients on Chronic Hemodialysis - Jaffe, Gabriel (1974)
The pharmacokinetics of tobramycin were studied in five patients with stable renal impairment, four patients requiring peritoneal dialysis, and four patients on chronic hemodialysis. The half-life of the drug varied with the level of the serum creatinine in the first group of patients, and the average volume of distribution was 15 liters. Only 49% of the administered dose of tobramycin was recovered during 36 h of peritoneal dialysis. The average clearance of tobramycin during hemodialysis was 49.1 ml/min, and 51.5% of the administered dose was recovered during a 6-h dialysis.